The Effectiveness of Implementing E-Filling, Inspection and Tax Sanctions on Taxpayer Compliance with Fiscal Service Quality as a Moderating Variable: Efektifitas Penerapan E-Filling, Pemeriksaan dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak dengan Kualitas Pelayanan Fiskus Sebagai Variabel Moderasi - Revina, Foni; Ernandi, Herman (Indonesian Journal of Innovation Studies, 2023)
This study aims to test the effectiveness of the implementation of E-Filling, Tax Examination and Sanctions on Taxpayer Compliance with Fiscal Service Quality as a Moderating Variable. The data for this study were obtained from questionnaires distributed to trading and industrial companies in Sidoarjo Regency. The sampling technique used is saturated sampling. The data analysis technique used in this research is Partial Least Square (PLS) and reliability test. The results of the tests carried out show that the application of E-Filling does not effectively affect taxpayer compliance with the quality of tax service services as a moderating variable. Tax audits and sanctions have an effective effect on taxpayer compliance with the quality of tax services as a moderating variable.